Raucous Twilight Pina Bausch's Kontakthof reviewed - Sansom, Bruce (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Review of Pina Bausch's Kontakthof. You know your parents have sex but you don't want to imagine it, and you certainly don't want to watch. PALABRAS CLAVE: Pina Bausch, Kontakthof.
Keywords: Bausch, Pina -- 1940-2009